If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 94 + -2x = 25x + 19 Reorder the terms: 94 + -2x = 19 + 25x Solving 94 + -2x = 19 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 94 + -2x + -25x = 19 + 25x + -25x Combine like terms: -2x + -25x = -27x 94 + -27x = 19 + 25x + -25x Combine like terms: 25x + -25x = 0 94 + -27x = 19 + 0 94 + -27x = 19 Add '-94' to each side of the equation. 94 + -94 + -27x = 19 + -94 Combine like terms: 94 + -94 = 0 0 + -27x = 19 + -94 -27x = 19 + -94 Combine like terms: 19 + -94 = -75 -27x = -75 Divide each side by '-27'. x = 2.777777778 Simplifying x = 2.777777778
| 8x-4=58 | | 7z-2=3z+6 | | 10-8x=82-29x | | 7x+5=54 | | 15-4e=3 | | 3e-3=18 | | 4x=88 | | 6x=88 | | -15-2x=13-9x | | 3y+3=18-2y | | 5-9x=45-23x | | 6x+39=16x-42 | | 5x+20=10x+10 | | 3(w-2)=12 | | 6a=17.4 | | 2a(3a-2)=0 | | 208-4x=32+20 | | t(4t-7)=0 | | 30+30*0+1=1 | | 5x-6=10x-16 | | 2x+36=12x-74 | | 7x-9=4x+12 | | =(6z^9-5z^4+4z^2+6)+(7z^7+4z^4-6z) | | 5x+7=77-7x | | 7x-2x=12 | | 3u+20=8u | | 6x+13=-9-10 | | 7g-15=g-3 | | 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 |